Analisis Kepuasan Mutu Pelayanan Imunisasi DPT di Wilayah Puskesmas Punti Kayu Palembang - selvi septiyah ningsih selvi; Chairil Zaman,; Ali Harokan (HEALTH CARE: JURNAL KESEHATAN, 2023)
The World Health Organization and the United Nations International Children's Emergency Fund say that every year 2.6 million babies worldwide cannot survive for more than one month. One million of them died at birth. Every age 0-11 months Indonesia is required to get complete basic immunization, one of which is DPT. This study aims to determine the satisfaction analysis of the quality of DPT immunization services in the Punti Kayu Palembang Health Center area in 2022. It was carried out in May - June 2022. This study was quantitative with a cross sectional design, the population of this study was the number of immunization visits in the Punti Kayu Health Center area of ​​Palembang City as many as 88 sample. Data collection and retrieval using a questionnaire. The results of statistical tests using the Chi-Square test and multiple logistic regression showed that there was a significant relationship (p value <0.05) for the variables of age (0.040), occupation (0.022), knowledge (0.003), attitude (0.041), and the role of the officer. health (0.001). There is no correlation between variables of gender (0.302), education (0.302), and income (0.104). From the results of the multivariate statistical test, the dominant factor was the role of health workers (p = 0.001; OR = 42,243). It is hoped that health workers in the Punti Kayu Palembang Health Center will always provide health promotion for postpartum mothers regarding complete basic immunization, especially DPT.